39th AIAA Thermophysics Conference 2007
DOI: 10.2514/6.2007-4269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Contact Charging on Spray Impingement Heat Transfer Performance and Spray Behavior

Abstract: The effects of contact charging on the heat transfer performance of a full-cone spray of the dielectric coolant, HFE-7000, has been studied using a Thick Film Resistor (TFR) heater with an active surface area of 1.46 cm 2 at a nozzle-to-heater spacing of 13 mm. Tests have been conducted at coolant flow rates between 1.3 and 6.8 GPH (1.4 x 10 -6 to 7.1 x 10 -6 m 3 /s), for heater power ranging from 0 to 60 Watts, yielding heat fluxes between 0 and 400 kW/m 2 . Voltage levels applied to the brass spray nozzle to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The results of Puterbaugh et al [14,15] suggested that the amount of dissolved air in FC-72 has an insignificant effect on CHF. Kreitzer et al [16][17][18] investigated body force effects on spray cooling by applying a high voltage coulombic, electrostatic, force to the spray cone, demonstrating small changes in heat transfer performance under specific conditions. Additionally, Glaspell [19] applied a Kelvin force, a magnetic field, to the spray, achieving results that provided a maximum heat transfer improvement of 5.2% at a 6 [kV] electrode voltage.…”
Section: List Of Tablesmentioning
confidence: 99%
“…The results of Puterbaugh et al [14,15] suggested that the amount of dissolved air in FC-72 has an insignificant effect on CHF. Kreitzer et al [16][17][18] investigated body force effects on spray cooling by applying a high voltage coulombic, electrostatic, force to the spray cone, demonstrating small changes in heat transfer performance under specific conditions. Additionally, Glaspell [19] applied a Kelvin force, a magnetic field, to the spray, achieving results that provided a maximum heat transfer improvement of 5.2% at a 6 [kV] electrode voltage.…”
Section: List Of Tablesmentioning
confidence: 99%
“…The atomization effect was infinitely close to the pure gasification diffusion. Kreitzer et al [ 24 ] demonstrated that conical electrodes were used to generate spray to reduce heat transfer and improve the cooling system. When the charging voltage exceeded 15 kV, a great change in the spray flow pattern was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Puterbaugh et al [14] and Puterbaugh [15] suggested that the amount of dissolved air in FC-72 has an insignificant effect on CHF. Kreitzer and Kuhlman [16], Kreitzer [17] and Kreitzer et al [16][17][18] investigated body force effects on spray cooling by applying an electrostatic force to the spray cone, demonstrating small changes in heat transfer performance under specific conditions. Additionally, Glaspell [19] applied a magnetic field to the spray, achieving results that provided a maximum heat transfer improvement of 5.2% at a 6 kV electrode voltage.…”
Section: Introductionmentioning
confidence: 99%